Narrative as topic and method in social research - Loseke, Donileen R. 1947- (Qualitative research methodS series, 2022)
Narrative research is an increasingly popular qualitative method across the social sciences. This book has two purposes: firstly to show students and researchers how to do research on narrative topics, particularly on questions about narrative productions of meaning, and secondly to explain some fundamentals of research methods suitable for exploring these topics. A final part of the book provides empirical examples of how such research is done. These chapters use small amounts of data to examine the analytic tasks of designing research questions, finding appropriate data, sampling decisions, contextualization, data categorization, and communicating study findings"--Provided by publisher.